2010
DOI: 10.1038/leu.2010.209
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of invasive fungal infections by a real-time panfungal PCR assay in immunocompromised pediatric patients

Abstract: Invasive fungal disease (IFD) is a life-threatening event in immunocompromised patients, and there is an urgent need for reliable screening methods facilitating rapid and broad detection of pathogenic fungi. We have established a two-reaction real-time PCR assay permitting highly sensitive detection of more than 80 fungal pathogens, covering a large spectrum of moulds, yeasts and Zygomycetes. To assess the clinical potential of the assay, more than 600 consecutive specimens from 125 pediatric patients carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 50 publications
(57 reference statements)
1
44
0
Order By: Relevance
“…The real-time PCR assay provides a high sensitivity and specificity for the detection of fungal DNA and rapidly identifies most of clinically relevant Aspergillus species (20). Many studies have reported the correlation between the presence of proven, probable, and possible criteria of IFIs according to the EORTC-MSG criteria and PCR results of the respective patients' sera (17,21,22). The results of the present study show 5/8 patients with proven and 5/6 patients with probable criteria.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The real-time PCR assay provides a high sensitivity and specificity for the detection of fungal DNA and rapidly identifies most of clinically relevant Aspergillus species (20). Many studies have reported the correlation between the presence of proven, probable, and possible criteria of IFIs according to the EORTC-MSG criteria and PCR results of the respective patients' sera (17,21,22). The results of the present study show 5/8 patients with proven and 5/6 patients with probable criteria.…”
Section: Discussionsupporting
confidence: 52%
“…followed by yeast infections including candidemia (20). The highest IFI-attributable mortality rates were associated with zygomycosis followed by fusariosis, aspergillosis, and candidemia (21).…”
Section: Discussionmentioning
confidence: 99%
“…Landlinger et al also evaluated the clinical potential of separate real-time qPCRs targeted a highly conserved region of the 28S rRNA multicopy gene, covering a wide spectrum of molds, yeasts, and the Mucormycetes (33). The sensitivity of the assay was revealed to be 96% (95% confidence interval, 82% to 99%).…”
Section: Discussionmentioning
confidence: 99%
“…The readout was performed by the use of a yeast-specific PCR of a panfungal real-time assay described earlier (11). Three independent experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Here we provide the first evidence for the presence of fungal DNA contaminants in lyophilized primers and TaqMan probes as well as in master mix solutions for real-time PCR analysis purchased at renowned biotechnology companies. Using a TaqMan-based panfungal PCR assay (11) established for sensitive screening of immunocompromised patients at risk for IFI, we detected traces of fungal DNA in several batches of the indicated reagents. To overcome the risk of false-positive PCR test results attributable to this issue, we have successfully applied a decontamination method based on the activity of a double-strand specific DNase (dsDNase).…”
mentioning
confidence: 99%